2014
DOI: 10.1371/journal.pone.0086750
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Levels and Its Variability in Incident Peritoneal Dialysis Patients: Associations with Mortality

Abstract: BackgroundAbnormal serum potassium is associated with an increased risk of mortality in dialysis patients. However, the impacts of serum potassium levels on short- and long-term mortality and association of potassium variability with death in peritoneal dialysis (PD) patients are uncertain.MethodsWe examined mortality-predictability of serum potassium at baseline and its variability in PD patients treated in our center January 2006 through December 2010 with follow-up through December 2012. The hazard ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 34 publications
2
70
3
1
Order By: Relevance
“…It has been reported that the variability of hemoglobin [29], serum calcium and phosphorus [30], as well as variability of serum potassium levels [9] are closely associated with clinical outcomes. However, few studies have investigated Mg variability in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the variability of hemoglobin [29], serum calcium and phosphorus [30], as well as variability of serum potassium levels [9] are closely associated with clinical outcomes. However, few studies have investigated Mg variability in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…CVSM was calculated as the ratio of SD to the mean of serum magnesium [9]. Patients were further divided into three classifications according to each tertile of magnesium CV: high variation group (CV ≥0.149 mmol/L), middle variation group (0.114 mmol/L ≤CV <0.149 mmol/L) and low variation group (CV <0.114 mmol/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 5.5 mEq/L is the reference worldwide accepted in laboratories, clinical trials, and real practice. [6][7][8] The incidence and prevalence of hyperkalemia, defined as potassium levels .5.5 mEq/L, vary depending on the patient characteristics. Its real prevalence is unknown, although an estimated prevalence in general population is among 2%-3%, and among 1%-10% in hospitalized patients.…”
Section: Prevalence Of Hyperkalemia In Hfmentioning
confidence: 99%
“…Szeto et al reported no association of residual renal function with hypokalemia in incident PD patients [5]. Moreover, Xu et al reported no association of baseline serum potassium levels with hypokalemia in incident PD patients [7].…”
Section: Introductionmentioning
confidence: 99%